2014
DOI: 10.1097/qad.0000000000000289
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of HIV latency by a newly modified Ingenol derivative via protein kinase Cδ–NF-κB signaling

Abstract: Objective Although HAART effectively suppresses viral replication, it fails to eradicate latent viral reservoirs. The ‘shock and kill’ strategy involves the activation of HIV from latent reservoirs and targeting them for eradication. Our goal was to develop new approaches for activating HIV from latent reservoirs. Design We investigated capacity of Ingenol B (IngB), a newly modified derivative of Ingenol ester that was originally isolated from a Brazilian plant in Amazon, for its capacity and mechanisms of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 69 publications
5
86
1
Order By: Relevance
“…54 Similar findings about the effects of IngB on HIV replication in cell culture models of HIV latency were reported, but involved the use of higher concentrations of IngB, up to 1 lM. 55 Interestingly, IngB also inhibited HIV replication by suppressing the expression of CD4, CCR5, and CXCR4.…”
Section: Ingenol Compoundssupporting
confidence: 61%
See 2 more Smart Citations
“…54 Similar findings about the effects of IngB on HIV replication in cell culture models of HIV latency were reported, but involved the use of higher concentrations of IngB, up to 1 lM. 55 Interestingly, IngB also inhibited HIV replication by suppressing the expression of CD4, CCR5, and CXCR4.…”
Section: Ingenol Compoundssupporting
confidence: 61%
“…52,53 Some of the ingenol derivatives, including ITA and I-3-A, enhanced HIV replication at nanomolar levels in chronically HIV-infected cells, depending on or independent of the PKC/NF-jB pathway. 52,53 We recently found that ingenol-3-hexanoate (IngB), a new ingenol compound from the Brazilian plant Euphorbia tirucalli, activated latent HIV LTR in the J-Lat cells in vitro as well as in U1 cells and was more potent than SAHA, JQ1, HMBA, or prostratin in reactivation of the provirus 54 ( Fig. 7).…”
Section: Ingenol Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found that a newly modified ingenol ester compound originally isolated from Euphorbia tirucalli, Ingenol B (IngB), reactivated latent viruses in J-Lat A1 cell lines and purified CD4 + T cells from HIV-1 infected patients under longterm HAART [65] . IngB can effectively promote HIV transcription through activation of the protein kinase C (PKC) δ-Serine 664-NF-κB pathway or through a direct increase in NF-κB expression.…”
Section: Ingenol B (Ingb)mentioning
confidence: 99%
“…The first class of compounds, including prostratin, bryostatin, and ingenol, induces cellular protein kinase C (PKC) signaling leading to migration of active NF-jB into the cell nucleus, which in turn promotes initiation of HIV mRNA transcription. 15,22,23 The second class of compounds, including HMBA plus the JQ1, I-BET, and I-BET151 bromodomain and extraterminal (BET) inhibitors, all release active P-TEFb in the cell, which in turn binds the HIV Tat transcriptional activator protein to drive elongation of HIV mRNA transcripts. 24,25 Thus, both types of compounds drive different stages of HIV transcription to enhance HIV mRNA expression.…”
Section: New Approaches To Shock Latently Infected Cellsmentioning
confidence: 99%